Tick paralysis with atypical presentation: isolated, reversible involvement of the upper trunk of brachial plexus. Issue 7 (22nd June 2006) - Engin, A; Elaldi, N; Bolayir, E; Dokmetas, I; Bakir, M
Abstract : Tick paralysis is a disease that occurs worldwide. It is a relatively rare but potentially fatal condition. The only way to establish the diagnosis is to carefully search for the tick paralysis. It is caused by a neurotoxin secreted by engorged female ticks. Tick paralysis generally begins in the lower extremities and ascends symmetrically to involve the trunk, upper extremities and head within a few hours. Although early-onset prominent bulbar palsy and isolated facial weakness without generalised paralysis are rare, there is no report in the English literature concerning isolated, reversible involvement of the upper trunk of brachial plexus caused by tick bite. We report a case of isolated, reversible involvement of the upper trunk of brachial plexus as a variant of tick paralysis. Diagnosis was confirmed with needle electromyography and nerve conduction examination. Within 2 weeks, the patient was fully recovered. The purpose of presenting this case is to remind clinicians that tick paralysis should be considered even in cases with atypical neurological findings admitted to the emergency department.